Retinol binding protein 4 correlates with and is an early predictor of carotid atherosclerosis in type 2 diabetes mellitus patients - Feng, Shangyong (Editorial Department of Journal of Biomedical Research, 2015)
The association of retinol binding protein 4 (RBP4) with atherosclerosis of the carotid artery in type 2 diabetes mellitus (T2DM) remains undefined. We aimed to investigate the correlation of RBP4 expression with atherosclerosis of the carotid artery in T2DM. A total of 1,076 subjects were investigated for intima-media thickness of the bilateral common carotid arteries, and they were divided into three groups: in group I, patients had normal neck vascular ultrasound, in group II, intimal carotid artery media thickness was equal to or more than 1 mm, and in group III, carotid artery plaque was present. Height, weight, blood pressure (BP), fasting plasma glucose (FPG), hemoglobin A1c (HbA1c), total cholesterol (TC), triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), apolipoprotein A-1 (apoA-1), apolipoprotein B (apoB) and lipoprotein (a) [Lp(a)] were determined by routine laboratory methods. RBP4 and high sensitivity C reactive protein (HsCRP) were measured by an enzyme-linked immuno-sorbent assay, and insulin concentration was measured by an electrochemiluminescence sandwich immunoassay. Duration of diabetes, waist and BP, FPG, HbA1c, TG, TC, LDL-C, APOB, Lp(a), HsCRP, RBP4 and homeostasis model assessment insulin resistance index (HOMA-IR) were significantly lower in group I than in the other two groups (P<0.01, P<0.01). Plasma levels of HbA1c, RBP4, LDL-C, TC, HOMA-IR, HsCRP and Lp(a), waist and BP were significantly increased in group III than in group II (P<0.01). Multivariate logistic regression analysis showed that there were seven factors associated with the occurrence of carotid artery atherosclerosis and its risks in descending order were: high LDL-C, high waist, high HsCRP, duration of diabetes, high HOMA-IR, HbA1c and high RBP4. Our finding supported that RBP4 was positively correlated with carotid atherosclerosis in patients with T2DM and could be used as an early predictor of cardiovascular disease.